Combination therapy for scalp angiosarcoma using bevacizumab and chemotherapy: a case report and review of literature - Yang, Ping; Zhu, Qi; Jiang, Fuqiang (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Bevacizumab, an angiogenesis inhibitor, is a recombined humanized monoclonal antibody against vascular endothelial growth factor and a promising therapeutic option for angiosarcoma management. This is a case report and review of the literature using bevacizumab and combination chemotherapy for angiosarcoma. The understanding of the effectiveness of combined therapy of bevacizumab and chemotherapy agents is still limited. The benefits of bevacizumab treatment for angiosarcoma will need to be weighed against the risks of venous thromboembolism in this population.